Manifestasi Budaya Popular Jepang di Amerika Serikat Melalui Anime Convention Sebagai Upaya Diplomasi Publik - Ghearaksa, Sekar; Sushanti, Sukma; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
Japan is a country that is currently widely known for its soft power. One of the soft powers possessed by Japan is anime. Anime is a typical Japanese animated series taken from the word 'Animation' with a typical Japanese pronunciation. Anime is currently enjoyed by many people from various parts of the world. As a forum for anime lovers, so an annual event called Anime Convention was created. Anime Convention is a fan convention with a primary focus on anime, manga, and Japanese culture. These conventions are usually events held at convention centers, hotels, or campuses. They attract many participants who are enthusiastic about anime and often participate in cosplay, where they dress up as their favorite anime characters. In fact, the biggest Anime Convention outside of Japan, is in the United States. In this case, Japan can pursue the Anime Convention as its Public Diplomacy in the United States. Anime Convention can be a form of Japanese public diplomacy, because it promotes Japanese culture and anime to a global audience. Anime conventions have been used to promote Japanese culture overseas, and they have been recognized as a strong economic commodity by the Japanese government. By introducing Japanese culture through anime, Japan has been able to encourage a better understanding of Japan among individual foreign nationals that forms the basis of public opinion and policymaking, in order to make Japan's image more positive.